Insufficiency Fracture of Medial Tibial Condyle: A Rare Case Report - Sibi Sanjay Baskaran; Swathi Balasubramanian; Balasubramanian Ganapathy (Journal of Orthopedics, Traumatology and Rehabilitation)
Insufficiency fractures (IFs) of medial tibial plateau are a rare presentation of acute knee pain. We present the case of a 65-year-old female who presented with acute knee pain with no history of trauma. X-rays were normal, but magnetic resonance imaging showed IF of medial tibial condyle. The patient was managed conservatively with protected weight bearing and antiosteoporosis therapy. Acute onset knee pain without any trauma should raise the suspicion of IF as one of the differential diagnosis.